STUDY OF THE CATALYTIC REACTION OF HYDRAZINOLYSIS OF ALIPHATIC CARBOXYLIC ACIDS - S.A.Dzhumadullayeva; A.B.Bayeshov (Academic Scientific Journal of Chemistry, 2019)
In this work, the reaction of hydrazinolysis of aliphatic carboxylic acid in the presence of an ionite catalyst is considered for the first time. The experiments were made in the static conditions. Previously, the corresponding butyl ether was obtained from the butyric acid, which in interaction with hydrazine formed a hydrazide. The influence of various factors (quantity of hydrazine hydrate, catalyst, butyl alcohol, temperature, reaction duration) on the formation of butyric acid hydrazide was studied. It reveals optimum conditions of synthesis under which the most hydrazide yield made 68%. As a result, the IR spectroscopic researches of the mechanism of hydrazinolysis reaction of the butyl ester of butyric acid with active centers of sulphonic cation-exchange. It is shown that the reaction proceeds with the formation of transition complexes on the surface of the cation exchange resin. The practical value of this work is to develop an effective method of butyric acid hydrazide preparation.